The complete conversion of cyclohexane into cyclohexanol and cyclohexanone by a simple silica-chromium heterogeneous catalyst - Adam, Farook; Retnam, Premalatha; Mohamed Iqbal, Mohammad Anwar (Elsevier, 2009)
Chromium and 4-(methylamino)benzoic acid (MBA) were incorporated into silica extracted from rice husk (RH). The chromium incorporated silica was labeled as RH-Cr and the chromium and MBA incorporated catalyst was labeled as RH-Cr-A. The specific surface area of RH-Cr and RH-Cr-A was determined to be 3.95 and 71.3 m2 g−1, respectively. The RH-Cr showed a wide pore distribution, while RH-Cr-A showed a very narrow pore structure. Both catalysts were shown to be amorphous by XRD. FTIR and EDX analysis showed that the amino benzoic acid and chromium had been incorporated into the silica matrix which resulted in nano-sized pores in RH-Cr-A. Complete conversion of cyclohexane was achieved in 6 h with H2O2 as the oxidant and acetonitrile as the solvent for both catalysts at 70 °C, yielding only cyclohexanone and cyclohexanol as products. The catalyst was reusable over many cycles.